Emotional Well-Being in Children with New-Onset Epilepsy - Goodwin, Shane W (2016)
Research suggests increased risk for adverse psychosocial outcomes and poor health-related quality of life and emotional well-being (EWB) in children with epilepsy compared to their healthy peers. The factors associated with poor EWB and the course of EWB in these children remains unclear. The objectives of this study were to: investigate the relationship between epilepsy-related and family factors and children’s EWB two years after the diagnosis of epilepsy; identify the average group trajectory of EWB in children with newly-diagnosed epilepsy over the first two years; and investigate whether we can identify subgroups of children with epilepsy that can be better represented with yet unidentified unique trajectories to describe their course of EWB, rather than using a single homogeneous group trajectory to represent all children. Data came from a multi-centre prospective cohort study of children with newly-diagnosed epilepsy from across Canada (Health-Related Quality of Life in Children with Epilepsy Study; HERQULES, n=373). EWB was measured using the Quality of Life in Childhood Epilepsy Questionnaire. Multiple regression assessed the relationship between epilepsy-related factors and EWB and tested possible mediation or moderation effects of family factors. Latent growth modeling and multinomial logistic regression was used to identify trajectories of EWB, the factors associated with each trajectory, and predictors of group membership to a particular trajectory. Behavioural problems, family functioning, family demands, and family resources were associated with poor EWB two-years post-diagnosis. Parental depressive symptoms were partially mediated by family functioning and by family demands. Family resources played a dual mediator/moderator role, moderating the relationship between severity of epilepsy and EWB. Two linear trajectories were identified, with the same set of factors associated with baseline EWB for both trajectories, but factors differed in their association with EWB across time for the two trajectories. The level of severity of epilepsy and family resources predicted a child’s membership to a particular trajectory. Poor EWB in children with epilepsy is associated with several epilepsy-related and family factors. After a diagnosis of epilepsy, family factors appear to be the most important influences on changes in EWB over time so efforts to strengthen the family environment may warrant attention